2011
DOI: 10.4049/jimmunol.1100987
|View full text |Cite
|
Sign up to set email alerts
|

Lung CD103+ Dendritic Cells Efficiently Transport Influenza Virus to the Lymph Node and Load Viral Antigen onto MHC Class I for Presentation to CD8 T Cells

Abstract: The uptake, transport, and presentation of Ags by lung dendritic cells (DCs) are central to the initiation of CD8 T cell responses against respiratory viruses. Although several studies have demonstrated a critical role of CD11blow/negCD103+ DCs for the initiation of cytotoxic T cell responses against the influenza virus, the underlying mechanisms for its potent ability to prime CD8 T cells remain poorly understood. Using a novel approach of fluorescent lipophilic dye-labeled influenza virus, we demonstrate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(144 citation statements)
references
References 40 publications
(52 reference statements)
7
137
0
Order By: Relevance
“…Another study demonstrated enhanced endocytosis by CD8 + DCs after effective killing of allogeneic cells by NK cells (53). Our data support the latter view by showing that NK cell-mediated killing of infected cells enhanced uptake of influenza A viral Ags by pulmonary DCs, especially the CD103 + DC subset, which was shown to be important in priming the CTL response during influenza A infection (30). This effect of perforinmediated cytotoxicity probably enhanced the pool of apoptotic cell-associated Ags, which are preferentially taken up by pulmonary CD103…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another study demonstrated enhanced endocytosis by CD8 + DCs after effective killing of allogeneic cells by NK cells (53). Our data support the latter view by showing that NK cell-mediated killing of infected cells enhanced uptake of influenza A viral Ags by pulmonary DCs, especially the CD103 + DC subset, which was shown to be important in priming the CTL response during influenza A infection (30). This effect of perforinmediated cytotoxicity probably enhanced the pool of apoptotic cell-associated Ags, which are preferentially taken up by pulmonary CD103…”
Section: Discussionsupporting
confidence: 83%
“…3). Next, we labeled influenza A with the lipophilic dye, DiD, which is attached to the lipid layer of the virus and has previously been used to follow influenza A virus infections in vivo (20,30). DiD is not incorporated into progenitor virus released from infected cells, and DiD therefore allowed us to track Ag uptake by DCs from primary infected cells.…”
Section: Perforin-dependent Generation Of Apoptotic Bodies Is Requirementioning
confidence: 99%
“…5). It is likely that the disappearing CD11c ϩ cells are dendritic cells which migrate to draining lymph nodes soon after contact with viral antigen, as recently demonstrated by others (30,31). Those authors further demonstrated that the migratory dendritic cells were not productively infected with influenza virus, which explains why IFN production by these cells was not inhibited by virus-encoded NS1.…”
Section: Cd11cmentioning
confidence: 61%
“…After natural infection, many cells in the lung become infected (69), and though dendritic cells (DC) can be infected and synthesize virus proteins and can migrate to the draining lymph node (34,35,70,71), there is limited evidence that these DC are able to release intact virions in the lymph node (72,73). Thus, the form of virus protein available for B cell receptor-mediated uptake in the draining lymph node may consist primarily of membrane fragments and proteins released from dying infected cells that either passively drain to the LN or are actively carried by migratory APC.…”
Section: Discussionmentioning
confidence: 99%
“…In the control group undergoing primary infection without prior CD4 T cell priming, there were no detectable NP-specific CD4 T cells. Interestingly, an apparent depletion of peptide-specific cells from this site occurred in the infected NP peptide-primed group, which may be an indication that central memory cells were recruited to sites of secondary antigen exposure, such as the MLN, the primary site of antigen access after intranasally inoculated respiratory infection (34)(35)(36)(37).…”
Section: Empirically Defined Immunodominant Influenza Virus Peptide Ementioning
confidence: 98%